Triterpenes from Archidendron clypearia (Jack) I.C.N. with anti-β-amyloid aggregation activity. Issue 16 (12th August 2021) - Wang, Yu-Xi; Duan, Zhi-Kang; Chang, Ye; Yan, Zhi-Yang; Wang, Xiao-Bo; Huang, Xiao-Xiao; Song, Shao-Jiang
Abstract: A new triterpene as well as five known compounds were isolated from the twigs and leaves of Archidendron clypearia (Jack) I.C.N. Their structures were established by comprehensive spectroscopic analyses including 1D, 2D NMR and HRESIMS data. The ability of all isolated compounds to inhibit β -amyloid aggregation was investigated by a ThT-based fluorometric assay. Among them, compounds 3 (67.8%) and 6 (77.7%) exhibited higher inhibitory activity than the positive (48.0%). In addition, molecular dynamics and molecular docking have been utilized to predict the detailed binding interaction between ligands and A β 1-42 . GRAPHICAL ABSTRACT: